Abominable Christmas - Keere, Chad van de.; Norkin, Susan; Olsson-Shear, Samantha; Shear, Mike.; Liotta, Ray.; Estevez, Emilio, 1962-; Lillard, Matthew, 1970-; Winter, Ariel, 1998-; Gould, Nolan; Bell, Drake, 1986-; Lynch, Jane, 1960-; Acres, Isabella; et al. (Santa Monica, CA : Distributed by ARC Entertainment, 2013)
After two abominable snowkids are chased from their mountain hideaway by a scientist determined to capture them, they're forced to spend Christmas with the most feared animal of them all--humans.
Originally produced as a motion picture in 2012.
Special features: episode of Artzooka! ;DVD trailers: Animals united, Joke.
Editor, Joshua Mark Guitar ; music, Michael Richard Plowman.
Voices: Ray Liotta, Emilio Estevez, Matthew Lillard, Ariel Winter, Nolan Gould, Drake Bell, Jane Lynch, Isabella Acres.
Primary: children 4-12; secondary: families.
Rating: Not rated.
Keywords: Yeti -- Juvenile films; Monsters -- Juvenile films; Christmas -- Juvenile films; Families -- Juvenile films; Animated films -- Juvenile films; DVD-Video discs; Video recordings for the hearing impaired; Children's films; Christmas films; Feature films; Animated films; Juvenile works